2019
DOI: 10.3390/en12091627
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Particle Swarm Based Optimization of an Air Jet Impingement System

Abstract: Air jet impingement systems have proven to be a very efficient way of heat transfer in single phase flows, which has allowed them to be applied in several industries. However, the complexity of the physical phenomena that take place in the cooling or heating processes makes the task of designing and sizing a system of this type very difficult. The objective of this work is to develop a methodology for the optimization of the impingement plate for electronic components cooling systems. The component chosen to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Considering the results, the study of low flows rates seemed necessary to find the maximum efficiency that could be reached with the impingement design of minimum crossflow tested, as well as the possibility that the design of zero crossflow could provide positive values of variation in the overall efficiency. The efficiency of the system could also be improved using air jet impingement plate optimization algorithms such as the one developed by Martínez-Filgueira et al [34]. This multi-objective algorithm could determine the optimum nozzle number, diameter, and other interest parameters, depending on the requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the results, the study of low flows rates seemed necessary to find the maximum efficiency that could be reached with the impingement design of minimum crossflow tested, as well as the possibility that the design of zero crossflow could provide positive values of variation in the overall efficiency. The efficiency of the system could also be improved using air jet impingement plate optimization algorithms such as the one developed by Martínez-Filgueira et al [34]. This multi-objective algorithm could determine the optimum nozzle number, diameter, and other interest parameters, depending on the requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Because the product temperature might rise quickly, dry moisture content should be considered in this system. Studies have shown that air impingement systems can cause localized hot and cold spots on a food surface (Martínez-Filgueira et al, 2019). The sample temperature distribution image of these hot- cold spots, which are more common in foods with a large surface area, can be seen in Figure 5.…”
Section: Use Of Air Impingement Technology In Different Food Processi...mentioning
confidence: 99%
“…where ρ is density, V is velocity, μ is dynamic viscosity, and D is diameter, respectively. Roughness of the surface affects the roughness Reynolds number, which in turn affects the properties of the boundary layer (Martínez-Filgueira et al, 2019). Heat transfer measurements have been studied in several studies of air impingement jets (Donaldson & Snedeker, 1971).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each particle keeps track of its coordinates in the problem space, which are associated with the best solution (fitness) it has achieved so far [19]. The authors have applied PSO successfully in other optimization problems related to energy applications, such as [21][22][23].…”
Section: Introductionmentioning
confidence: 99%